RANCANGAN MESIN SIKAT KARPET DENGAN MODIFIKASI TABUNG CAIRAN DETERJEN - Anderson, Sir; Amri, Khairul; Hafni, Ferdi Nanda (Jurnal Ilmiah Poli Rekayasa, 2023)
Now, washing carpets no longer requires a lot of human power. Just one person can wash carpets on a large scale at the same time as three human workers. By using this carpet brush machine, the job of cleaning carpets will be easier and faster. The aim of designing this machine is a form of innovation and creativity in a carpet brush machine with an electric motor drive. The machine is made with the addition of a detergent channel tube to make work easier and increase efficiency. The working principle of this carpet brushing machine is that when the motor is turned on, a pulley with a size of Ø 76.2 mm will rotate with a rotation of 1400 rpm, followed by a belt with a size of 24 inches to rotate the pulley on the shaft with a rotation of 703.5 rpm with a pulley size of Ø 152 mm. The rotation will be continued by the shaft, and the brush will rotate to clean up dirt or stains on the carpet. In making this machine, we obtained a motor power of ½ HP and a rotation of 1400 rpm. This machine has dimensions of 580x380x980 mm and uses a belt and pulley transmission with brush components. This carpet washing machine is used for MSME businesses (micro, small and medium businesses)